Frozen in time [compact disc, unabridged] : an epic story of survival and a modern quest for lost heroes of World War II - Zuckoff, Mitchell (HarperAudio, 2013)
On November 5, 1942 a U.S. cargo plane on a routine flight slammed into the Greenland ice cap. Four days later, a B-17 on the search-and-rescue mission became lost in a blinding storm and also crashed. The U.S. military launched a second daring rescue operation, but the plane sent to find the men flew into a severe storm and vanished. This account details the fate of the survivors and their would-be saviors.